Effectiveness of multiherbal leaf extract for the treatment of Oreochromis niloticus infected with pathogens - Iko Imelda Arisa; Ulfa Rahmi; Nurfadillah Nurfadillah; Sari Afriani; Julianda Fatma (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
The many herbal plants in Indonesia that contain antimicrobial substances such as Calotropis gigantea, Moringa oleifera and Cassia alata L. leaves are attractive and have the potential to be used to prevent and treat bacterial diseases in fish. This study aims to determine the effectiveness of administering a combination of multi-herbal ingredients, namely M. oleivera, C. gigantea and C. alata L. leaves in the treatment of O. niloticus tilapia infected with the pathogenic bacteria S. agalactiae. The experimental design used a completely randomized design with 6 treatment levels and 3 replications, namely treatment A (Fish that were not infected with S. agalactiae), B (Fish infected with S. agalactiae), C (Fish infected with S. agalactiae + soaked in thistle leaf extract 800 ppm+ Moringa leaf extract 1000 ppm)), D (Fish infected with S. agalactiae + soaked in C. gigantea leaf extract 800 ppm + C. allata leaf extract 10 ppm), E (Fish infected with S. agalactiae +soaked in Moringa leaf extract 1000 ppm + C. allata leaf extract 10 ppm) and F (Moringa leaf extract 1000 ppm+C. gigantea leaf extract 800 ppm + C. allata leaf extract 10 ppm). The results showed that the combination of M. oleivera, C. gigantea and C. alata L. extracts had a significant effect (P0.05) on the survival rate ofO. niloticus. Treatment (E), combination of M. oleivera leaf extract 1000 ppm + C. alata L leaf extract 10 ppm, showed the fastest healing of the body and the highest survival rate of tilapia, namely 80%.Keywords:Multi herbal leavesPatoghenImunnity